Performance Analysis of a Low-Pass Filter for Virtual Camera Rotation Stabilization Using a Gyroscope Sensor - Dila Dahlia; Tito Pinandita; Sigit Sugiyanto; Elindra Ambar Pambudi (Politeknik Piksi Ganesha Indonesia, 2026)
The use of mobile device cameras often suffers from rotational instability caused by jitter and sudden orientation changes, reducing visual quality and user experience in virtual camera applications. This study evaluates the effectiveness of a low-pass filter in stabilizing gyroscope-based virtual camera rotation. Experiments were conducted using an iPhone 12 under six movement scenarios: slow rotation, fast rotation, random movement, walking, stair climbing, and motorcycle riding. Euler angle and inter-frame jitter data were analyzed before and after filter implementation. The results show that the low-pass filter significantly reduces rotational jitter in five of the six scenarios. The greatest improvement was observed during walking, with an 86.55% reduction, followed by fast rotation (72.21%) and random movement (68.87%). These findings confirm that the low-pass filter effectively suppresses high-frequency rotational disturbances, enhancing virtual camera stability and providing a practical foundation for developing more reliable gyroscope-based rotation stabilization systems on mobile devices.